2019
DOI: 10.1177/1553350619862097
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Indocyanine Green Fluorescence Angiography in Reconstructive Flap Surgery: A Systematic Review and Ex Vivo Experiments

Abstract: Background. Indocyanine green angiography (ICGA) offers the potential to provide objective data for evaluating tissue perfusion of flaps and reduce the incidence of postoperative necrosis. Consensus on ICGA protocols and information on factors that have an influence on fluorescence intensity is lacking. The aim of this article is to provide a comprehensive insight of in vivo and ex vivo evaluation of factors influencing the fluorescence intensity when using ICGA during reconstructive flap surgery. Methods. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 76 publications
(349 reference statements)
2
34
1
1
Order By: Relevance
“…Our selection of an IV dose of 2.5 mg/cat was based on our previous clinical experience in dogs. In man, IV ICG administration is reported as a standard fixed dose (2.5 mg‐25 mg) or as milligram per body weight dose (0.025‐0.5 mg/kg) 30 . In a recent systematic review of ICG fluorescence angiography, Pruimboom et al 30 reported that a fixed dosing method was used in 60% of studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our selection of an IV dose of 2.5 mg/cat was based on our previous clinical experience in dogs. In man, IV ICG administration is reported as a standard fixed dose (2.5 mg‐25 mg) or as milligram per body weight dose (0.025‐0.5 mg/kg) 30 . In a recent systematic review of ICG fluorescence angiography, Pruimboom et al 30 reported that a fixed dosing method was used in 60% of studies.…”
Section: Discussionmentioning
confidence: 99%
“…In man, IV ICG administration is reported as a standard fixed dose (2.5 mg-25 mg) or as milligram per body weight dose (0.025-0.5 mg/kg). 30 In a recent systematic review of ICG fluorescence angiography, Pruimboom et al 30 reported that a fixed dosing method was used in 60% of studies. The dose we selected was well within the reported dog and cat dose ranges (0.54 mg/kg for cat 1, 0.29 mg/kg for cat 2) and provided good visualization of the perforating vessel in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in future patient selection and to further understand perfusion patterns, healthy volunteers should be taken into account as well. With regard to the NIR fluorescence intensity analysis, the use of normalized time-intensity curves seems rational since intensity-related parameters are prone to multiple influencing factors, including camera distance and ICG dosage [30,31]. This normalization minimizes the effect of these influencing factors on the measured intensity and contributes to a narrower distribution, as seen in the time-intensity curves in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Wearable technology with heads-up displays has entered the medical field and been used for various medical purposes such as navigation surgery (Shao et al, 2014), education (Guze, 2015), and vital sign monitoring (Liebert, Zayed, Aalami, Tran, & Lau, 2016). In the setting of the reconstructive surgery, near-infrared fluorescence (NIRF) imaging using indocyanine green (ICG), also known as ICG angiography, is used predominantly to assess tissue perfusion in transferred flap (Pruimboom et al, 2019). Our goal in this letter is to describe a new effective method for intraoperative ICG angiography for flap surgery using wearable smart glasses.…”
Section: Dear Editormentioning
confidence: 99%